Democracy and economic growth in Sub-Saharan Africa: A panel data approach - Jaunky, Vishal (Physica-Verlag GmbH und Co., 2013)
This paper studies the link between democracy and economic development for 28 countries of Sub-Saharan Africa for the period 1980-2005 in a panel data framework. A democracy index constructed from the Freedom House indices. A variety of panel data unit root and cointegration tests are applied. The variables are found to be integrated of order one and cointegrated. The Blundell-Bond system generalized methods-of-moments is employed to conduct a panel error-correction mechanism based causality test within a vector autoregressive structure. Economic growth is found to cause democracy in the short-run, while bidirectionality is uncovered in the long-run. In addition, the long-run coefficients are estimated through the panel fully modified ordinary least squares and dynamic ordinary least squares methods. Democracy has a positive impact on GDP and vice versa. These results lend support to the virtuous cycle hypothesis. © 2012 Springer-Verlag.